2013
DOI: 10.6009/jjrt.2013_jsrt_69.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Patient Exposure Doses in Diagnostic Radiography in 2011 Questionnaire

Abstract: We report here the results of a dose evaluation based on information obtained in a 2011 questionnaire as compared with an investigation made in 2007. Briefly, in general radiography, the dose used in most examinations in 2011 was lower than in 2007. However, since the entrance surface dose for chest X-rays showed an increase, there is a need to standardize the taking of digital images to be able to decrease the dose. Although computed tomography dose index volume (CTDIvol) in CT examinations was higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The CTDI vol values for each anatomical region in this study were mostly very similar to those of the other countries, although the 75th percentile of the CTDI vol for the head and abdomen in adults was noticeably higher in Japan than in other countries. These CTDI vol values have not changed since the 2011 survey 15 ( Figure 3). This would ideally prompt an earnest attempt to reduce the diagnostic radiation dose of the adult head and abdomen.…”
Section: Full Paper: Survey Of Volume Ct Dose Index In Japan In 2014 Bjrmentioning
confidence: 99%
See 3 more Smart Citations
“…The CTDI vol values for each anatomical region in this study were mostly very similar to those of the other countries, although the 75th percentile of the CTDI vol for the head and abdomen in adults was noticeably higher in Japan than in other countries. These CTDI vol values have not changed since the 2011 survey 15 ( Figure 3). This would ideally prompt an earnest attempt to reduce the diagnostic radiation dose of the adult head and abdomen.…”
Section: Full Paper: Survey Of Volume Ct Dose Index In Japan In 2014 Bjrmentioning
confidence: 99%
“…Therefore, a new set of Japanese DRLs has become an urgent necessity. In 2011, Asada et al 15 reported mean CTDI vol values for the head (non-helical and helical), chest and upper abdomen of both adults and children, which were obtained using a nationally distributed questionnaire. The aims of this study are to propose a new set of Japanese DRLs for 2014 and to study the impact of tube voltage and the type of reconstruction algorithm on patient doses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…examinations at levels that have been found to be safe (Asada et al, 2013). Every aspect of radiology has been enhanced by DL and ML.…”
Section: Radiologymentioning
confidence: 99%